1998
DOI: 10.1056/nejm199803053381002
|View full text |Cite
|
Sign up to set email alerts
|

Variations in theNRAMP1Gene and Susceptibility to Tuberculosis in West Africans

Abstract: Genetic variation in NRAMP1 affects susceptibility to tuberculosis in West Africans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
497
6
8

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 672 publications
(531 citation statements)
references
References 27 publications
20
497
6
8
Order By: Relevance
“…Nevertheless, at the clinical level, the NRAMP1 gene is thought to influence susceptibility to Mycobacterium tuberculosis, with four variants within the gene being significantly associated with acquisition of infection with tuberculosis and leprosy. 20 Although in general HLA-DR genes/gene products have been shown to play a major immunoregulatory role in immune response against M. tuberculosis antigens and in resistance or susceptibility to other infective agents, HLA-DR11 in particular has not been identified as a prominent player. Variance in HLA-DR has been shown to modulate either a Type 1 or Type 2 CD4+ response to M. leprae HSP 21 and it is well established that HLA-DR plays a role in the binding efficiency of various peptides, with variable binding efficiencies being reported for HLA-DR11.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, at the clinical level, the NRAMP1 gene is thought to influence susceptibility to Mycobacterium tuberculosis, with four variants within the gene being significantly associated with acquisition of infection with tuberculosis and leprosy. 20 Although in general HLA-DR genes/gene products have been shown to play a major immunoregulatory role in immune response against M. tuberculosis antigens and in resistance or susceptibility to other infective agents, HLA-DR11 in particular has not been identified as a prominent player. Variance in HLA-DR has been shown to modulate either a Type 1 or Type 2 CD4+ response to M. leprae HSP 21 and it is well established that HLA-DR plays a role in the binding efficiency of various peptides, with variable binding efficiencies being reported for HLA-DR11.…”
Section: Discussionmentioning
confidence: 99%
“…55 Because of the critical role of Nramp1 in the mouse model of typhoid fever, the human homologue of mouse NRAMP1 was investigated in resistance to typhoid fever in humans. Despite the fact that NRAMP1 contributes clearly to the risk and the progression of mycobacterial infections in humans, 7,[64][65][66] no allelic association was identified between NRAMP1 and typhoid fever susceptibility in humans in southern Vietnam. 67 However, these studies do not preclude a role for NRAMP1 in susceptibility to human Salmonella infections because of the known effect of the ethnic genetic background on the expression of disease susceptibility.…”
Section: Nramp1mentioning
confidence: 94%
“…Indeed, only two published studies document whole genome scans for QTLs that may affect host resistance to M. tuberculosis infection, 17,26 and the loci mapped in our study appear distinct from those mapped by these two groups. The Chr.1 Nramp1 locus plays a key role in host resistance against several intracellular infections in mice, including several mycobacterial species, 27 and NRAMP1 alleles have been associated with susceptibility to tuberculosis, 9 and leprosy in humans. 28 However, Trl-1 on Chr.1 identified in our study (map position 74 cM; 1999 Chr.1 committee report; www.informatics.jax.org) 29 On the other hand, linkage of susceptibility to infection with high doses of M. tuberculosis (1 × 10 6 , i.v.)…”
Section: Genes and Immunitymentioning
confidence: 99%
“…The genetic analysis of a complex trait such as susceptibility to tuberculosis is extremely difficult in humans due to variable pathogenicity determinants of the bacterium, unequal exposure, incomplete penetrance, phenocopies, locus heterogeneity, and polygenic effects. 4 Case-control studies in endemic areas of tuberculosis using candidate genes have revealed association of susceptibility to disease with alleles of genes encoding the macrophage natural resistance protein NRAMP1, 9 the vitamin D receptor, 10 and HLA-DQ 11 in specific populations. However, the overall effect of these genes is acknowledged to be small, and other genes are certain to play a role in susceptibility to human tuberculosis.…”
Section: Introductionmentioning
confidence: 99%